Evaluation of the quality and suitability of groundwater for agricultural and drinking purposes in the Koraiyar River basin, Tamil Nadu, India - Moorthy, S Sundara; Raj, N Jawahar (Brawijaya University, 2025)
In the Koraiyar basin, located within the districts of Tiruchirappalli and Pudukkottai in Tamil Nadu, India, groundwater samples were investigated to evaluate their quality and appropriateness for both drinking and agricultural purposes. Groundwater is a dynamic source for sustaining human life and various activities; however, its overuse and deteriorating quality pose significant challenges. Groundwater faces threats from various factors, including climate change, changes in land use, and population growth, all of which impact both the quantity and quality of available groundwater. Salinity exerts a substantial influence on various parameters, as indicated by the strong correlation between electrical conductivity (EC) and many other factors. It is inferred that pre-monsoon samples exhibit slightly lower quality compared to post-monsoon samples, although they remain suitable for drinking, with only a few exceptions. Most of the samples are safe to drink and use in agriculture because they are within allowable levels. Total dissolved solids (TDS) and total hardness (TH) data show that the groundwater samples are mostly of the pre-monsoon hard to extremely hard type. The Gibbs plot's evaporation zone contains samples, indicating that surface activities like agricultural runoff and other human-induced variables like home sewage dumping can contaminate groundwater. With the exception of samples showing average salinity and high sodium concentrations, all other samples are suitable for irrigation across various soil types.